Effect of different structural flaxseed lignans on the stability of flaxseed oil-in-water emulsion: An interfacial perspective. (30th September 2021) - Cheng, Chen; Yu, Xiao; Huang, Fenghong; Peng, Dengfeng; Chen, Hongjian; Chen, Yashu; Huang, Qingde; Deng, Qianchun
Graphical abstract: Highlights: Different structural flaxseed lignans inhibited FO oxidation in HSPC-emulsions. SECO and FLEH enhanced the physical stability of emulsions. The free radical membrane permeation was highly inhibited by SECO and FLEH. The mechanism mainly related to the interactions between HSPC and flaxseed lignans. The flaxseed lignans decreased the lipolysis by lipase during simulated digestion. Abstract: The influences of the different structural flaxseed lignans on flaxseed oil (FO) emulsions during storage and digestion were investigated, focusing on their interfacial behavior. From perspective of interface, more than 60% of secoisolariciresinol (SECO) and the acidic hydrolysates of flaxseed lignan macromolecule (FLEH) were located on the interface of FO emulsions. It improved the stability of FO emulsions both during storage and digestion by inhibiting of free radical penetration and improving their targeted antioxidative activity. By comparison, the secoisolariciresinol diglucoside (SDG) and the alkaline hydrolysates of flaxseed lignan macromolecule (FLE) largely located in the aqueous and exerted lower antioxidative efficiency in emulsions. Moreover, SDG, SECO, FLE and FLEH slowed down the digestive rate of FO in emulsions, which might be due to flaxseed lignans inhibited the activity of digestive enzymes. These findings suggested that the different structural flaxseed lignans had the potential as antioxidants in emulsions during storage and digestion.